1998
DOI: 10.1016/s1383-5866(97)00053-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phenylalanine onto polymeric resins: equilibrium, kinetics and operation of a parametric pumping unit

Abstract: Adsorption of D, L-Phenylalanine onto polymeric adsorbents (Amberlite XAD-4 and XAD-16; Sephabeads SP206 and SP207) was studied. Adsorption equilibrium isotherms were measured by batch equilibration at 15 and 40°C showing the possibility of using a parametric pumping technique for aminoacid purification/recovery. Dynamic studies in a laboratory adsorption column Amicon Column (22 x 500 mm) were carried out to further screen adsorbents and obtain mass transfer parameters to be used in the modeling, simulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Nonionic polymeric resins have been previously successfully used for phenol and phenolic derivatives adsorption [19][20][21][22]. Table 1 summarizes the data supplied by the manufacturers on the physical characteristics of the resins used in this work.…”
Section: Chemicals and Adsorbentsmentioning
confidence: 99%
“…Nonionic polymeric resins have been previously successfully used for phenol and phenolic derivatives adsorption [19][20][21][22]. Table 1 summarizes the data supplied by the manufacturers on the physical characteristics of the resins used in this work.…”
Section: Chemicals and Adsorbentsmentioning
confidence: 99%
“…Adsorption is also the process employed for the removal of phenylalanine from protein hydrolysates in the preparation of Phe-free dietary formulas for treatment of phenylketonuria patients (Clark, Alves, Franca, & Oliveira, 2012). Many studies have been reported in the scientific literature dealing with the adsorption of phenylalanine on materials such as activated carbons, zeolites, ion exchangers, polymeric resins and others (Díez, Leitão, Ferreira, & Rodrigues, 1998;Titus, Kalkar, & Gaikar, 2003;Garnier et al, 2007;Piao, Liu, Li, & Wang, 2009;Ghosh, Badruddoza, Uddin, & Hidajat, 2011;Fei-Peng, Zhao-Di, Li, & XiaoQing, 2012). However, high costs are associated with the production and regeneration of such adsorbents and these costs could be reduced by the use of low-cost adsorbents (Clark et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to reduce costs is the use of residues from the food industry in the development of protein hydrolysates. However, the PHE contents in the produced hydrolysate must be reduced to acceptable levels, usually by adsorption (Díez, Leitão, Ferreira, & Rodrigues, 1998;Long et al, 2009;Titus, Kalkar, & Gaikar, 2003). Thus, high costs are still associated with the PHE removal step given the use of synthetic adsorption materials, and such costs could be reduced by the use of residue-based adsorbents .…”
Section: Introductionmentioning
confidence: 99%